2014
DOI: 10.1177/105268461402400203
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Information-Processing Systems of Leaders and Their Relation to Student Learning Outcomes

Abstract: Research has shown that school principals who display transformational leadership are likely to influence organizational commitment and job satisfaction (Koh, 1990), and this in turn is thought to influence student learning outcomes. Based on a sample of experienced educational leaders (n = 88), this study examined if transformational leadership and information-processing systems according to cognitive-experiential self-theory predict teachers' job satisfaction and student learning outcomes. The rational syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Cognitive‐Experiential Theory (CET; Epstein, 2014, previously Cognitive Experiential Self Theory, CEST; Epstein, 1994) suggests that it is possible to assess individual differences in thinking styles at the level of semi‐malleable traits. Recent research suggests that thinking styles as conceptualised in CET are related to leadership levels (Akinci & Sadler‐Smith, 2013), leadership styles (e.g., Cerni, Curtis, & Colmar, 2008), workplace influence behaviours (Curtis & Lee, 2013), conflict handling styles (Cerni, Curtis, & Colmar, 2012), and organisational outcomes (Cerni, Curtis, & Colmar, 2014a).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive‐Experiential Theory (CET; Epstein, 2014, previously Cognitive Experiential Self Theory, CEST; Epstein, 1994) suggests that it is possible to assess individual differences in thinking styles at the level of semi‐malleable traits. Recent research suggests that thinking styles as conceptualised in CET are related to leadership levels (Akinci & Sadler‐Smith, 2013), leadership styles (e.g., Cerni, Curtis, & Colmar, 2008), workplace influence behaviours (Curtis & Lee, 2013), conflict handling styles (Cerni, Curtis, & Colmar, 2012), and organisational outcomes (Cerni, Curtis, & Colmar, 2014a).…”
Section: Figurementioning
confidence: 99%
“…As implied above, a limitation of the current research is the use of single raters of both leadership and thinking styles. Although Norris and Epstein (2011) found strong correlations between self‐rated and other‐rated thinking styles using the REIm and the REIm‐o, especially for rational thinking, it has been argued that thinking styles are best captured by self‐reports (Cerni et al, 2014a). In short, it is reasonable to assume that people know their own minds better than others' do.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In a number of recent studies, connections have been found between individual differences in information‐processing styles, as conceptualized in CET, and leadership styles, leadership behaviors, and related outcomes (e.g., Atwater & Yammarino, ; Cerni et al, ; Cerni, Curtis, & Colmar, , , , , ; Curtis & Lee, ; Dubinsky, Yammarino, & Jolson, ; Humphreys & Zettel, ). These findings were a source of inspiration to develop the Cognitive‐Experiential Leadership Model.…”
Section: Cognitive‐experiential Theorymentioning
confidence: 99%
“…First, in Cerni et al’s (, Study 1), leaders’ rational thinking was positively correlated with subordinates’ extra effort, effectiveness, and satisfaction, as rated by their leaders. Second, Cerni et al () investigated more objective organizational outcomes and found that school leaders’ preferences for rational thinking and conscientiousness, a subscale of behavioral coping, were significantly positively correlated with the final‐year performance of senior students in their respective schools. Finally, Epstein () reported that executives who outperformed their peers tended to be higher in emotional coping, lower in the destructive thinking style of personal superstitious thinking, and much higher in behavioral coping.…”
Section: The Cognitive‐experiential Leadership Modelmentioning
confidence: 99%
“…CELM suggests that combining the rational system with the constructive use of the experiential system (Epstein, 2001) results in thinking adaptively. This could then enhance transformational leadership techniques (Cerni, Curtis & Colmar, 2010a;2010b), choice of conflict-handling styles (Cerni, Curtis & Colmar, 2012), choice of influencing tactics (Curtis & Lee, 2013), and organizational outcomes (Cerni, Curtis & Colmar, 2014;Theeboom, Beersma & van Vianen, 2014).…”
Section: Cognitive-experiential Theory (Cet)mentioning
confidence: 99%